A Narratological Analysis of the Strategic Affective Enlistment in Hardy’s Major Wessex Novels - Saeid Behnoud; Negar Sharif; Zahra Bordbari (Critical Literary Studies)
The present study focuses on the strategic process of enlisting the readers’ empathetic responsiveness in Thomas Hardy’s major Wessex novels. The analytical perspective draws on Suzanna Keen’s theories in affective narratology; it intends to uncover the stylistic strategies of affective impressionism in the Wessex narratives. The methodological procedure is grounded in the qualitative appraisal of the emotive aspects of Hardy’s realistic representations through critical discourse analysis. The research approach is influenced by the recent mind theories in cognitive science, emphasizing emotional perception as the most significant determinant of the gestalt of interpretations. The semi-fictional world of Wessex capitalizes on an insight into the primacy of emotive sensibility over cognitive rationality. The authorial intentionality in the Wessex narratives aspires to propagate human compassion by resorting to the literary application of the empathy-altruism hypothesis. The melioristic agenda for edification via investment in the readers’ emotive capacities saturates the narratives’ impressionistic composition. The manipulation of the narrative consciousness foci in the major Wessex novels enables Hardy to maintain his readers’ empathetic identification with his characters’ predicaments in a philosophical context. Moreover, the tagged characterization of the protagonists establishes the intended impressions of their temperament and demands the corresponding empathetic responses from the readers.